(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article talks about the methods of determining the levels of formation of students’ aesthetic outlook. Based on pedagogical data, the author analyzed the problem based on existing scientific literature and methods of determining the levels of formation of the aesthetic outlook of students.